Training, practice, and career considerations in forensic psychology: results from a field survey of clinical and non-clinical professionals in the United States - Casey LaDuke; Casey LaDuke; David DeMatteo; David DeMatteo; Eve M. Brank; Antoinette Kavanaugh; Antoinette Kavanaugh (Frontiers in Psychology)
The current field survey describes the identities, training, practices, and careers of 351 U.S. forensic psychologists. Findings are presented for clinical forensic psychologists (n = 323) with additional consideration for those working in institutions (n = 119), private practice (n = 107), or both (n = 90), and separately for non-clinical forensic psychologists (n = 35). The sample was predominantly middle-aged, White, and female. Participants reported various training paths to the field, and professional settings and activities in the field. Student loan debt was common and significant in clinical Forensic psychologists. Income was generally high, with trends in higher incomes for private practice, board certification, urban areas, and certain geographic regions. Gendered income disparities were common, particularly among those later in their careers and in private practice, with relative parity only observed among early-career clinical forensic psychologists in institutions. Career satisfaction was generally high, with some important barriers noted. Overall, the limited representation of those with historically marginalized cultural identities restricted further consideration and understanding of these important factors in the field. Additional data and discussion are provided for these and other areas of demographics and lived experiences, training and related financial considerations, professional practices (including settings, activities, and clinical test use), and career considerations (including income, benefits, retirement planning, and satisfaction). Together, these data and related discussions offer important insights for prospective and current trainees entering the field, professionals seeking to navigate and advance their careers, and field leaders aiming to contribute to the ongoing development of forensic psychology.